IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS’ PROFESSIONAL SPEECH COMPETENCE - Gulnoz Maqsudova; Nozimaxon Mamadjanova; Muxabbat Sharipova; Shahribonu Tohirova (The Bioscan, 2024)
The ability to communicate effectively in a professional setting is crucial for students preparing to enter the workforce. This paper examines current methodologies for developing students' professional speech competence and proposes enhancements based on recent research and practical applications. We analyze existing pedagogical strategies, identify gaps in the current approaches, and offer a revised methodology that integrates contemporary communication theories and technological tools. Our findings suggest that a multi-faceted approach, combining traditional instructional methods with innovative techniques, can significantly enhance students' professional speech skills, thereby better preparing them for their future careers.